The Relation Between Cognitively Measured Executive Functions and Reported Self-Regulated Learning Strategy Use in Adult Online Distance Education - Meijs, Celeste; Gijselaers, Hieronymus J. M.; Xu, Kate M.; Kirschner, Paul A.; De Groot, Renate H. M. (Frontiers in Psychology, 2021)
While executive functions and self-regulated learning strategy use have been found to be related in several populations, this relationship has not been studied in adult online distance education. This is surprising as self-regulation and, thus, using such strategies, is very important here. In this setting, we studied the relation between basic executive functions (i.e., working memory and shifting; measured with cognitive tests) and reported self-regulated strategy use (i.e., management of time and effort, complex and simple cognitive strategy use, contacts with others, and academic thinking) within an correlational design with 889 adult online distance students. In this study, we performed regression analyses and took age and processing speed into consideration as processing speed and EFs decrease with age, whereas self-regulation is reported to increase with age. Cognitively measured working memory was not related to reported SRL-strategy use in adult ODE students. Thus, even though the SRL-components within the strategies seem to elicit working memory reported SRL-strategy use is not related to the functioning of this basic EFs (measured with cognitive tests). This means that if SRL-strategy use needs to be increased in adult ODE students, training of working memory might not be an effective manner for achieving that goal. Better shifting and processing speed were related to less reported SRL-strategy use, which might suggest that SRL-strategies might be used to compensate for lower shifting (in academic thinking) and lower processing speed (in simple cognitive strategy use and contacts with others). With increasing age, the number of contacts with peers or teachers decreases. This latter finding might be of relevance during the pandemic since contacts with others is importance during lockdown.